Korrekcija morfofunkcional'nych pokazatelej serdca i kardiogemodinamiki sportsmenov pod dejstviem nejroendokrinnogo adaptogena "Milajf" - Necaeva, G. I.; Smitienko, O. L.; Dejatlova, A. Ju.; Kornjakova, V. V. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The aim of this paper was to study the dynamics of morphofunctional parameters of a heart under the action neuroendocrine adaptogen "Mylife". 32 19±1 years aged male athletes, engaged by cyclic kinds of sports: swimming, ski races, track and field athletics, cycling and speed skating. Criteria of the selection: the sports experience not less than 3 years, the sports category from 1st and higher, the hyperactivity of the tone of the sympathetic segment of the vegetative nervous system. The variety of biologically active preparations, which are coming nearer on the chemical compound to complex membrane structure of a human cell, has determined the multivalency of "Mylife" influence on metabolic-endocrine-immune processes, rendering adjusting influence on all kinds of a metabolism. The restoration of the processes of neurohumoral regulation and the power resources of the myocardium was reflected in the improvement of the contractile ability, functions of a relaxation and positive stimulations of a heart. The balanced complex of amino acids, vitamins and the macrocells, contained in the "Mylife", promoted the normalization of the broken homeostasis and the establishment of the high level of compensative mechanisms. The restoration of the biopower processes improves the compensative opportunities of an organism promoting the work of a heart in the more economical mode.